Strategies to Drive Photo-Fenton Process at Mild Conditions for the Removal of Xenobiotics from Aqueous Systems - Santos-Juanes, Lucas; M. Amat, Ana; Arques, Antonio (Current Organic Chemistry, 2017)
The aim of this paper is to provide an overview on the different approaches that can be employed to drive a photo-Fenton process under mild conditions, using both heterogeneous and homogeneous iron sources. For this purpose, sections are devoted to the following strategies: a) addition of iron at low concentrations; b) using the matrix of the effluent in order to avoid deactivation of iron; c) addition of chemical auxiliaries to form photoactive complexes with iron, such as carboxylates, chelating agents and humic-like macromolecules; d) strategies leading to the application of heterogeneous photo-Fenton process, by using iron-based solid particles or by hosting iron on different supports and; e) using heterogeneous iron sources as a reservoir for constant dosing of homogeneous iron photocatalyst. In particular, the review will focus on the elimination of emerging pollutants (e.g. drugs, personal care products or pesticides at low concentrations) which are the effluents where applying neutral photo-Fenton seems especially meaningful, although relevant works with other families of pollutants are also considered.
Keywords: photo-Fenton